2022
DOI: 10.1002/cphc.202200791
|View full text |Cite
|
Sign up to set email alerts
|

Band Edges Engineering of 2D/2D Heterostructures: The C3N4/Phosphorene Interface

Abstract: We investigate the interface between carbon nitride (C3N4) and phosphorene nanosheets (P‐ene) by means of Density Functional Theory (DFT) calculations. C3N4/P‐ene composites have been recently obtained experimentally showing excellent photoactivity. Our results indicate that the formation of the interface is a favorable process driven by Van der Waals forces. The thickness of P‐ene nanosheets determines the band edges offsets and the charge carriers’ separation. The system is predicted to pass from a nearly ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 84 publications
0
3
0
Order By: Relevance
“…Motivated by its structural similarity between CN and graphene, the hybridization between them has been enormously attempted with the expectation of an unusual electron coupling at the interface of the hybrid structure. 292–294 With the heterointerface between graphene and CN, computational results suggest that there is no band gap and Dirac cone at the Γ point, underscoring high electrical conductivity upon hybridization (Fig. 17b and c).…”
Section: Band Gap Engineering Of G-cnmentioning
confidence: 99%
“…Motivated by its structural similarity between CN and graphene, the hybridization between them has been enormously attempted with the expectation of an unusual electron coupling at the interface of the hybrid structure. 292–294 With the heterointerface between graphene and CN, computational results suggest that there is no band gap and Dirac cone at the Γ point, underscoring high electrical conductivity upon hybridization (Fig. 17b and c).…”
Section: Band Gap Engineering Of G-cnmentioning
confidence: 99%
“…Common methods for calculating the band edges and offsets (valence band offset and conduction band offset) of the two materials include the plane-averaged electrostatic potential method [36,37] and core-level energies method. [20,38] Combining with the results of energy band structure and DOS of the BP/GCN heterojunction, we calculated the potentials of the VBM and CBM of BP and GCN in the BP/GCN heterojunction using the method proposed by Toroker et al [39] The calculation results are shown in Figure 8. The VBM potential of BP is 0.60 V (vs normal hydrogen electrode (NHE)), and the CBM potential of BP is À0.96 V (vs NHE).…”
Section: Resultsmentioning
confidence: 99%
“…[ 19 ] Furthermore, Ran et al [ 16 ] found that electrons transfer from g‐C 3 N 4 to phosphorene upon contact, resulting in a strong electronic coupling in the 2D/2D few‐layer phosphorene/g‐C 3 N 4 nanosheet Van der Waals heterojunction. Additionally, Di Liberto et al [ 20 ] reported that the thickness of the P‐ene component has a significant impact on the positioning of the band edges, and adjusting the thickness can potentially enhance the efficiency of C3N4/P‐ene interfaces in charge separation. Despite exhibiting excellent photocatalytic performance, the fundamental reasons for the superior performance of BP/GCN heterojunctions are not yet fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…The second relevant example concerns phosphorene nanosheets. The bulk material displays a very small band gap, 0.5 eV, with a hybrid functional (0.4 eV experimentally) [35,125,172], and the gap increases up to 1.5 eV with a single monolayer [35]. Another class of materials where the band gap is a fundamental property is lead halide perovskites.…”
Section: Application Of Computational Approaches To Predict Quantum S...mentioning
confidence: 99%
“…Similarly, CsPbBr 3 particles have been interfaced with a few nm thick TiO 2 coating resulting in a stable device in environmental conditions, and enhanced photo-electrochemical activity, due to the positioning on the band edges [33]. C 3 N 4 /phosphorene interfaces have been generated with thin phosphorene film and they have been used for photocatalytic H 2 reaction [34][35][36]. Another important example is that of supported metal particles on oxides.…”
Section: Introductionmentioning
confidence: 99%